The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jcp.30728
|View full text |Cite
|
Sign up to set email alerts
|

Post natal expression of Prx1 labels appendicular restricted progenitor cell populations of multiple tissues

Abstract: Currently, there is no consensus whether there is a single or multiple postnatal stem cell population(s) that contribute to skeletal homeostasis and postnatal bone formation. A known population of cells that express Prx1 contributes to postnatal bone formation. Prx1 expression also connotes calvaria and appendicular tissues during embryonic development. A transgenic tamoxifen inducible Prx1 reporter mouse was used for lineage tracking, to characterize the postnatal contribution of Prx1 expressing cells in skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Within the nonhematopoietic population isolated from the muscle, periosteum and bone marrow, the percentage of Prx1 cells were 33.22 ± 9.70%, 5.58 ± 1.70%, and 0.58 ± 0.13% (Figure 4B). Overall, Prx1-expressing cells have the highest fraction in skeletal muscle, which aligns with the observations we obtained from our previous histological analysis (Bragdon et al, 2022).…”
Section: Molecular Profiling Of the Prx1 Cells From Different Skeleta...supporting
confidence: 92%
See 3 more Smart Citations
“…Within the nonhematopoietic population isolated from the muscle, periosteum and bone marrow, the percentage of Prx1 cells were 33.22 ± 9.70%, 5.58 ± 1.70%, and 0.58 ± 0.13% (Figure 4B). Overall, Prx1-expressing cells have the highest fraction in skeletal muscle, which aligns with the observations we obtained from our previous histological analysis (Bragdon et al, 2022).…”
Section: Molecular Profiling Of the Prx1 Cells From Different Skeleta...supporting
confidence: 92%
“…Advances with genetic mouse models have revealed several markers that can be used to define various populations of SSCs, including Nestin, LepR, Mx1, αSMA, Periostin, Cathespin K, Cxcl12, Prx1 (Méndez-Ferrer et al, 2010;Park et al, 2012;Greenbaum et al, 2013;Zhou et al, 2014;Debnath et al, 2018;Duchamp de Lageneste et al, 2018). Published work along with our studies showed Prx1 expressing cells connote a multi-potential postnatal SSC population that retained its embryonic tissue specification, localized to multiple sites such as bone marrow, periosteum, and muscle within the appendicular regions and contributes to homeostatic maintenance, fracture repair, and HO (Batista et al, 2019;Julien et al, 2021;Bragdon et al, 2022).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Consistently, most Prx1 + SSPCs are present in the long bone periosteum during embryonic and postnatal development. Prx1 + cells are present during embryonic development restricted to the mesoderm which becomes mesenchymal cells postnatally without losing their embryonic tissue specification and thus have SSPC properties (Du et al, 2013;Bragdon et al, 2022). These pnPrx1 + P-SSPCs are known to inhibit adipogenesis by activating TGFβ signaling (Du et al, 2013).…”
Section: Unique Regulation Of Periosteal Sspcs (P-sspcs)mentioning
confidence: 99%